Theoretical study of the mechanism of two successive N-methylene C–H bond activations on a phosphine-tethered N-heterocyclic carbene on a triruthenium carbonyl cluster. Issue 102 (19th October 2016) - Yan, Jing; Han, Zhe; Zhang, Dongju; Liu, Chengbu
Abstract : DFT calculations clarify the mechanism details of successive N -methylene C–H bond activations on N-heterocyclic triruthenium carbene complexes. Abstract : Recently the Kennedy group reported a unique successive N -methylene C–H bond activation on N-heterocyclic triruthenium carbene complexes. Here, density functional theory calculations have been performed on this reaction to clarify the molecular-level mechanism of the two C–H bond activations. The calculated results indicated that the reaction occurs sequentially through the following steps: phosphine ligand dissociation from the Ru center followed by rearrangement of ligands on Ru center, the first C–H bond oxidative addition to Ru, the elimination of the first CO ligand with recoordination of the phosphine ligand, the second CO ligand elimination followed by the second C–H bond activation, and hydride migrations between Ru centers. The rate-determining step is the first C–H bond activation, which needs to overcome a barrier of 37.9 kcal mol −1 .